Price theory and its uses - Watson, Donald Stevenson (New York, Houghton Mifflin, 1972)
This edition is an intermediate text on price theory retains main features of the second, along with its organization. The many changes, most of them small are intended to heighten clarity and interest.
Includes bibliographical references.
osa 23/01/19
Loans
Keywords: Microeconomics; Prices